2011
DOI: 10.1002/lsm.21053
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effect of low‐level laser therapy (LLLT) on the acute lung inflammation induced by intestinal ischemia and reperfusion: Action on anti‐ and pro‐inflammatory cytokines

Abstract: The results indicate that the LLLT attenuates the i-I/R-induced acute lung inflammation which favor the IL-10 production and reduce TNF generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 37 publications
2
58
0
1
Order By: Relevance
“…10,29 IIR challenge results in translocation of bacteria and toxins, which amplifies systemic inflammation and oxidative stress, and leads to ALI and ARDS. 2,3,4,32 Oxidative stress is a disturbance in the balance between the production of free radicals and antioxidant defense systems. Free radicals are generated in the form of reactive oxygen species (ROS), including superoxide anions, hydrogen peroxide, hydroxyl radicals, and singlet oxygen.…”
Section: Role Of Nrf2 Q-t Meng Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…10,29 IIR challenge results in translocation of bacteria and toxins, which amplifies systemic inflammation and oxidative stress, and leads to ALI and ARDS. 2,3,4,32 Oxidative stress is a disturbance in the balance between the production of free radicals and antioxidant defense systems. Free radicals are generated in the form of reactive oxygen species (ROS), including superoxide anions, hydrogen peroxide, hydroxyl radicals, and singlet oxygen.…”
Section: Role Of Nrf2 Q-t Meng Et Almentioning
confidence: 99%
“…2,3 The lungs are often the most frequently affected organs by IIR, and in some instances it leads to the development of acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). 4 Despite numerous attempts to improve the outcome in patients with ARDS, a mortality rate around 50% is still encountered. 5 Ischemic post-conditioning (IPo) has been demonstrated to be beneficial following ischemia/reperfusion (IR) injury in the heart, brain, liver, kidney, and spinal cord, 6 and its mechanical interventions against reperfusion injury relate to multiple and interacting components in endogenous protective mechanisms.…”
mentioning
confidence: 99%
“…Furthermore, LLLT modulates the expression of some inflammatory mediators such as Cyclooxygenase-2 (COX-2), tumor necrosis factor α (TNFα), interleukin 1β, (IL1β), and interleukin 10 (IL10) [7,15,16]. Moreover, it has been demonstrated that LLLT can stimulate VEGF expression and angiogenesis [6,17].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, LLLT has shown interesting results regarding the repair of muscle damage, increase wound healing, reducing pain, and inflammation both in animal models [22,[24][25][26][27] as well as in humans [28,29]. Several studies have demonstrated the effectiveness of LLLT in treating the inflammatory process, and these studies indicated the modulating property of laser light toward anti-inflammatory and proinflammatory mediators [30][31][32]. However, other studies have shown a failure of LLLT in conditions involving joint damage [33,34].…”
Section: Discussionmentioning
confidence: 99%